Comparative Susceptibility of Channel Catfish, Blue Catfish, and their Hybrid Cross to Experimental Challenge with Bolbophorus damnificus (Digenea: Bolbophoridae) Cercariae. Issue 2 (13th May 2014) - Griffin, Matt J.; Reichley, Stephen R.; Khoo, Lester H.; Ware, Cynthia; Greenway, Terrence E.; Mischke, Charles C.; Wise, David J.
Abstract: The digenetic trematode Bolbophorus damnificus has been implicated in significant losses in catfish aquaculture since the late 1990s. The complex life cycle sequentially involves the American white pelican Pelecanus erythrorhynchos, the marsh rams horn snail Planorbella trivolvis, and Channel Catfish Ictalurus punctatus . Research supports anecdotal reports from the industry, suggesting that the hybrid of Channel Catfish×Blue Catfish I. furcatus is less susceptible to disease agents that have been historically prohibitive to Channel Catfish production, namely the gram‐negative bacteria Edwardsiella ictaluri and Flavobacterium columnare, as well as the myxozoan parasite Henneguya ictaluri . This current research compared the susceptibility of Channel Catfish, Blue Catfish, and their hybrid cross to an experimental challenge by B. damnificus. Fish were exposed to 0, 100, 200, and 400 B. damnificus cercariae per fish, and the numbers of metacercariae per fish were determined 14 d postchallenge. Metacercariae were recovered from all challenged fish. There were no significant differences among fish groups challenged with the same dose, suggesting Channel and Blue Catfish and their hybrid are comparably susceptible to B. damnificus infection. As such, it is recommended that producers raising hybrid catfish remain diligent in controlling populations of the snail intermediate host to prevent production losses attributed to B. damnificus, especially when loafing pelicans have been observed at the aquaculture operation. Received October 22, 2013; accepted January 5, 2014